Assessment of platelet biology in equine patients with systemic inflammatory response syndrome. (March 2021) - Ehrmann, Carolin; Engel, Julia; Moritz, Andreas; Roscher, Katja
In addition to maintaining hemostasis, platelets have an important role in modulating innate and adaptive immune responses. A low platelet count has been found to be a negative prognostic factor for survival in humans and horses with critical illnesses, such as sepsis or systemic inflammatory response syndrome (SIRS). Decreased platelet aggregation, caused by in vivo activation, has been found in human patients with severe sepsis. In our prospective controlled study, we assessed platelet biology in blood samples from 20 equine SIRS cases and 120 healthy control horses. Platelet variables such as platelet count, large platelet count, clumps, plateletcrit, mean platelet volume, and mean platelet component concentration were analyzed by laser flow cytometry (Advia 2120) from K3 EDTA blood and from citrate blood. Hirudin blood samples were analyzed by impedance aggregometry (Multiplate analyzer; Roche) for platelet aggregation, including spontaneous aggregation and aggregation by 4 different agonists: adenosine diphosphate (ADPtest), ADP + prostaglandin E1 (ADPtestHS), arachidonic acid (ASPItest), and collagen (COLtest). SIRS cases had significantly lower platelet counts in K3 EDTA blood ( p < 0.0001) compared to control horses. There were no significant differences in aggregation values between SIRS cases and controls. Non-surviving SIRS horses did not have statistically significant lower platelet counts or lower aggregation values for COLtest, ADPtest, or ADPtestHS compared to surviving SIRS horses, although 5 non-survivors were thrombocytopenic.